USING STORY MAPPING STRATEGY TO IMPROVE THE ABILITY OF THE SECOND GRADE STUDENTS OF SMA TRI BHAKTI PEKANBARU IN COMPREHENDING NARRATIVE TEXTS - Novi Khairani Khairani; Syofia Delfi Delfi; Supriusman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Teachers tend to improve the students’ ability by applying strategies. One of them is the topic of this article. This article is based on a research report about using story mapping strategy to improve students’ ability in comprehending narrative texts. The aimof this research was to know whether or not using story mapping strategy could improve students’ ability in comprehending narrative texts and how it could improve the ability. Classroom action research was designed in two cycles at 39 students of XI-1 Science of SMA Tri Bhakti Pekanbaru as the participant of this research. The data were collected through reading comprehension test, observation sheet, and field note. This research found that story mapping strategy could improve the students’ ability in comprehending narrative texts. Students’ mean score improved from 40 in pre-test to 66 in post-test 1, and to 79,7 in post-test 2. It is in line with the activeness of students that improved from 83% in cycle 1 to 96,5% in cycle 2. Story mapping strategy helps students in visualizing the narrative texts. It analyzes each part of the story and tells how it relates to each other. The students were introduced to the essential part to make them comprehend the text easily. This research recommended that teachers could use story mapping strategy to improve students’ ability in comprehending narrative texts since it was an effective strategy by providing the structure and organization of the texts.Key words: story mapping strategy, ability, narrative text